Plastic scintillation fiber and its manufacturing method
Patent Information
- Application Number
- JP2022556401
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-15
- Filing Date
- 2021-07-01
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-07-01
AI Technical Summary
【0029】 本発明により、高感度でX線やγ線を検出可能であって、生産性に優れたプラスチックシンチレーションファイバを提供できる。
Smart Images

Figure 0007645899000001 
Figure 0007645899000002 
Figure 0007645899000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a plastic scintillation fiber and a method for producing the same. [Background technology]
[0002] Conventional plastic scintillating fibers (PSFs) are plastic fibers in which the outer surface of the scintillator core is covered with a cladding layer with a lower refractive index than the core, and are primarily used for radiation detection. The core is usually made of a polymeric material in which an organic phosphor is added to a base material having an aromatic ring, such as polystyrene or polyvinyltoluene. The cladding layer is made of a polymeric material with a low refractive index, such as polymethyl methacrylate or fluorine-containing polymethyl methacrylate.
[0003] The principle of radiation detection using plastic scintillation fiber is explained below. The core substrate of scintillation fiber has aromatic rings, and when irradiated radiation crosses the scintillation fiber, it absorbs part of the energy due to re-emission of secondary particles in the core, and emits it as ultraviolet light. If no phosphor is added to the core substrate, this ultraviolet light is absorbed by the core substrate itself and disappears without being transmitted within the core.
[0004] In plastic scintillation fibers, this ultraviolet light is absorbed by the phosphor added to the core substrate, and light of longer wavelengths is re-emitted. Therefore, by selecting an appropriate phosphor, the light can be converted to light of longer wavelengths, such as blue light, which is less likely to be absorbed by the core substrate, and transmitted through the fiber. The light transmitted through the fiber is detected by a detector connected to one or both ends.
[0005] Thus, scintillation fibers have two functions, emitting light by detecting radiation and transmitting light, and are used in applications such as calculating the position and amount of radiation that has passed through. In such scintillation fibers, it is important to efficiently convert the ultraviolet light emitted from the core to a long wavelength and transmit it over long distances.
[0006] On the other hand, plastic wavelength conversion fiber (WLSF: Wavelength Shifting Fiber) is also widely used along with scintillation fiber. Wavelength conversion fiber is used in combination with, for example, a plastic scintillator that emits blue light. A groove or hole is made in a plate-shaped or rod-shaped plastic scintillator, and a wavelength conversion fiber that absorbs blue light and converts it to green light is embedded in it.
[0007] In large-scale, large-area detectors, it can be difficult to transmit light from individual scintillators to an external photoelectric detector (such as a photomultiplier tube) located at a distance due to light attenuation and spatial constraints. In such cases, wavelength conversion fibers that are thin, easy to bend, and capable of long-distance transmission are preferably used. Many wavelength conversion fibers can be freely laid out to the external photoelectric detector.
[0008] The core of the wavelength conversion fiber is made of polystyrene resin or polymethyl methacrylate resin, in which a phosphor for wavelength conversion (hereinafter also referred to as "wavelength conversion phosphor") is dissolved. In the wavelength conversion fiber, the scintillation light incident from the external scintillator is absorbed by the phosphor in the core, and the light is efficiently wavelength converted and transmitted within the fiber. The scintillator to be combined with the wavelength conversion fiber is not limited to plastic scintillators, and inorganic scintillators with high detection sensitivity for X-rays, gamma rays, etc. can also be used.
[0009] In this way, the wavelength conversion fiber can easily collect the scintillation light emitted from a large-area or long scintillator. Also, the wavelength conversion fiber can transmit light whose wavelength has been converted in the core and can be freely connected to a photoelectric detector.
[0010] Here, detection of X-rays and gamma rays is difficult with plastic scintillators made only of light elements because of the low probability of interaction with X-rays and gamma rays, resulting in low detection sensitivity. For example, inorganic scintillators are used. Examples of inorganic scintillators include BaF2, CsI, CaF2, CeF3, and Bi4Ge3O 12 , Y2SiO5, Y3Al l5 O 12 , Bi4Ge3O 12 , PbWO4, CdWO4, Gd2SiO5:Ce 3+ ,Lu2SiO5:Ce 3+ Many such as are known.
[0011] However, inorganic scintillators are not very transparent, with an attenuation length of several mm, and cannot transmit the emitted light (i.e., scintillation light) over long distances. In addition, there are restrictions on the crystal size, making it difficult to transmit light to a photoelectric detector using inorganic scintillators.
[0012] In addition, as disclosed in Non-Patent Document 1, there are cases where the detection sensitivity for X-rays and gamma rays is improved by adding a lead compound or the like to a plastic scintillator. However, as the concentration of the added heavy metal element increases, the transparency of the plastic scintillator decreases, making it unsuitable for use in large sizes.
[0013] For this reason, in Patent Documents 1-3, etc., a wavelength conversion fiber is arranged along the end face or surface of a scintillator, and the detection light is transmitted to a photoelectric detector through the wavelength conversion fiber. By using a wavelength conversion fiber, the detection light can be transmitted over a longer distance. Here, in all of Patent Documents 1 to 3, detection that places importance on spatial resolution, such as the image detection disclosed in Patent Document 2 in particular, requires a lot of post-processing to combine the scintillator and the wavelength conversion fiber. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] International Publication No. 2015 / 064588 [Patent Document 2] JP 2011-141239 A [Patent Document 3] JP 2015-72227 A [Non-patent literature]
[0015] [Non-Patent Document 1] Japanese Journal of Applied Physics 54, 102202 (2015) Summary of the Invention [Problem to be solved by the invention]
[0016] In conventional plastic scintillation fibers, the core itself emits scintillation light and transmits light to the photoelectric detector, so the core must be highly transparent. Therefore, it is not possible to obtain a plastic scintillation fiber with improved detection sensitivity for X-rays and gamma rays by incorporating a compound containing a heavy metal element into the core to increase the probability of interaction with X-rays and gamma rays.
[0017] On the other hand, conventional scintillation detectors using wavelength conversion fibers require post-processing to combine the scintillator and the wavelength conversion fiber. Furthermore, when detecting images, it is necessary to separate and combine each scintillator for each of the many wavelength conversion fibers, which makes the processing extremely difficult.
[0018] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a plastic scintillation fiber that is capable of detecting X-rays and γ-rays with high sensitivity and has excellent productivity. [Means for solving the problem]
[0019] A plastic scintillation fiber according to one aspect of the present invention comprises: an outermost layer including a resin containing a compound of a heavy metal element and having scintillation properties; a core provided inside the outermost layer and including at least one type of phosphor that absorbs scintillation light generated in the outermost layer and converts the wavelength of the light to a longer wavelength; a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core; The wavelength conversion fiber including the core and the cladding layer and the outermost layer covering the outer peripheral surface of the wavelength conversion fiber are integrally formed.
[0020] When a plastic scintillation fiber is irradiated with X-rays or gamma rays, charged particles such as electrons or positrons are generated through interactions such as the photoelectric effect, the Compton effect, and electron pair creation, resulting in scintillation light. In the plastic scintillation fiber of the present invention, since the outermost layer contains a compound of a heavy metal element, the probability of the above-mentioned interaction is improved, and the detection sensitivity to X-rays and gamma rays is improved compared to conventional plastic scintillation fibers. Here, since the outermost layer does not require high transparency required for transmitting light like the core, the compound of a heavy metal element can be added at a high concentration.
[0021] In addition, since the wavelength conversion fiber including the core and clad layer and the outermost layer covering the outer surface of the wavelength conversion fiber are integrally formed, the post-processing required in the past to combine the scintillator and the wavelength conversion fiber is no longer necessary. That is, it is possible to provide a plastic scintillation fiber that has high detection sensitivity for X-rays and γ-rays and is highly productive.
[0022] The outermost layer may contain at least one phosphor that absorbs the scintillation light and converts it to a longer wavelength, thereby suppressing self-absorption of the scintillation light by the resin having scintillation properties, and further improving the detection sensitivity of X-rays and gamma rays.
[0023] The heavy metal element may be lead or bismuth. In the outermost layer, the compound of the heavy metal element may be copolymerized with the resin having scintillation properties.
[0024] The wavelength conversion fiber and the outermost layer may be integrally formed by a drawing process, which further improves productivity. A protective layer for protecting the outermost layer may be integrally formed on the outer side of the outermost layer, thereby improving durability and the like.
[0025] Furthermore, the clad layer may have a multi-clad structure including an inner clad layer and an outer clad layer covering the outer peripheral surface of the inner clad layer and having a lower refractive index than the inner clad layer, thereby widening the total reflection angle and resulting in higher light emission.
[0026] A reflective layer may be provided on the outer side of the outermost layer or the protective layer. By reflecting the scintillation light emitted in the outermost layer or the light whose wavelength has been converted in the core on the reflective layer, the scintillation light is less likely to leak out from the side surface of the fiber, resulting in high luminescence. The reflective film may be a metal film. This configuration allows a high reflectance to be obtained with a thin thickness. On the other hand, since the metal film has a high probability of interacting with X-rays and gamma rays, by increasing the thickness, the sensitivity to X-rays and gamma rays is improved, and the utilization efficiency of the light wavelength-converted in the core and the scintillation light emitted in the outermost layer is also improved, resulting in high light emission.
[0027] A method for producing a plastic scintillation fiber according to one aspect of the present invention includes the steps of: an outermost layer including a resin containing a compound of a heavy metal element and having scintillation properties; a core provided inside the outermost layer and including at least one type of phosphor that absorbs scintillation light generated in the outermost layer and converts the wavelength of the light to a longer wavelength; A method for manufacturing a plastic scintillation fiber comprising: a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core, a step of inserting a second cylinder for the cladding layer into a first cylinder for the outermost layer, and inserting the core rod into the second cylinder to prepare a preform; and a step of drawing the preform while heating it.
[0028] A method for producing a plastic scintillation fiber according to one aspect of the present invention includes the steps of: an outermost layer including a resin containing a compound of a heavy metal element and having scintillation properties; a core provided inside the outermost layer and including at least one type of phosphor that absorbs scintillation light generated in the outermost layer and converts the wavelength of the light to a longer wavelength; A method for manufacturing a plastic scintillation fiber comprising: a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core, The outermost layer is coated on the surface of the wavelength conversion fiber including the core and the cladding layer. Effect of the Invention
[0029] According to the present invention, it is possible to provide a plastic scintillation fiber that is capable of detecting X-rays and γ-rays with high sensitivity and has excellent productivity. [Brief description of the drawings]
[0030] [Figure 1] 1 is a cross-sectional view of a plastic scintillation fiber according to a first embodiment. [Diagram 2] FIG. 4 is a cross-sectional view of a plastic scintillation fiber according to a modified example of the first embodiment. [Diagram 3] FIG. 11 is a cross-sectional view of a plastic scintillation fiber according to another modified example of the first embodiment. [Figure 4]1 is a perspective view showing a manufacturing method of a plastic scintillation fiber according to a first embodiment. [Diagram 5] 1 is a perspective view showing an application example of a scintillation fiber according to the first embodiment. FIG. [Figure 6] The emission spectrum of para-terphenyl added to the outermost layer and the absorption and emission spectra of the wavelength conversion phosphor BBOT. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Hereinafter, specific embodiments to which the present invention is applied will be described in detail with reference to the drawings. However, the present invention is not limited to the following embodiments. In addition, the following description and drawings are appropriately simplified for clarity of explanation.
[0032] (Embodiment 1) <Structure of plastic scintillation fiber> A plastic scintillation fiber according to a first embodiment of the present invention will be described with reference to Fig. 1. Fig. 1 is a cross-sectional view of the plastic scintillation fiber according to the first embodiment. As shown in FIG. 1, the plastic scintillation fiber according to the first embodiment includes an outermost layer 1, a core 2, and a cladding layer 3.
[0033] The outermost layer 1 is made of a resin containing a compound of a heavy metal element and having scintillation properties. For example, the resin is a transparent resin containing a phosphor that absorbs the scintillation light emitted from the resin and converts it to a longer wavelength, in addition to the compound of a heavy metal element. Here, a heavy metal element is a metal element whose specific gravity is 4 or more by itself. When the outermost layer 1 contains a wavelength conversion phosphor, self-absorption of the scintillation light by the transparent resin is suppressed, and the detection sensitivity of X-rays and gamma rays is further improved.
[0034] The outermost layer 1 only needs to be sufficiently luminous and transparent so that the scintillation light can penetrate the cladding layer 3 and enter the central core 2; high transparency is not required, but it is desirable that the outermost layer 1 is as transparent as possible. The thickness of the outermost layer 1 may be made thicker in order to obtain the required detection sensitivity for X-rays and gamma rays. Even if the outermost layer 1, which is a scintillator layer, has low transparency, long-distance transmission is possible as long as the central core 2, which is responsible for optical transmission, has high transparency.
[0035] The core 2 is provided inside the outermost layer 1, and is made of a transparent resin with a high refractive index that contains at least one type of phosphor that absorbs the scintillation light generated in the outermost layer 1 and converts it to a longer wavelength. The refractive index of the transparent resin constituting the core 2 is preferably 1.5 or more.
[0036] The cladding layer 3 covers the outer peripheral surface of the core 2 and is made of a transparent resin having a lower refractive index than the core 2. Here, the wavelength conversion fiber composed of the core 2 and the cladding layer 3 and the outermost layer 1 covering the outer peripheral surface of the wavelength conversion fiber are integrally formed. For long-distance transmission as an optical fiber, the transparency of the cladding layer 3 is as important as the transparency of the core 2. For long-distance transmission, the transparency of the outermost layer 1 is not so important.
[0037] To perform long-distance transmission as an optical fiber, the thickness of the cladding layer 3 is preferably 3 μm to 100 μm, which is sufficiently thicker than the depth of the evanescent wave of the transmitted light seeping out from the core into the cladding layer 3. It is sufficient that the thickness of the cladding layer 3 is sufficiently thicker than the depth of the evanescent wave of the transmitted light seeping out into the cladding layer 3.
[0038] It is desirable that the wavelength conversion phosphor contained in the core 2 has an absorption spectrum that matches the wavelength of the scintillation light generated in the outermost layer 1, and the fluorescence spectrum to be wavelength converted is as far away from the absorption spectrum as possible. Furthermore, the core 2 may contain a second phosphor that further converts the wavelength, for example, to match the wavelength sensitivity of a photoelectric detector such as a photomultiplier tube (PMT) or an avalanche photodiode (APD). Details of the phosphor will be described later.
[0039] In the plastic scintillation fiber according to the first embodiment, the outermost layer 1 contains a compound of a heavy metal element having a high probability of interaction with X-rays and gamma rays. Therefore, when irradiated with X-rays or gamma rays, more charged particles such as electrons and positrons are generated in the outermost layer 1 due to the photoelectric effect, the Compton effect, electron pair creation, etc. than in the conventional plastic scintillation fiber composed only of light elements such as carbon, hydrogen, and oxygen. As a result, scintillation light is generated in the outermost layer 1 made of a resin having scintillation properties, and the scintillation light is absorbed by the inner core 2, converted in wavelength, and optically transmitted. Therefore, X-rays and gamma rays can be detected with higher sensitivity than in the conventional plastic scintillation fiber.
[0040] That is, the plastic scintillation fiber according to the first embodiment is a scintillator-integrated plastic wavelength conversion fiber in which the scintillator (outermost layer 1) and the plastic wavelength conversion fiber (core 2 and cladding layer 3) are integrated together. Therefore, the post-processing of combining the scintillator and the wavelength conversion fiber, which was previously required, is not necessary, and the productivity is improved dramatically and the cost is reduced compared to the conventional method.
[0041] A protective layer (not shown) for protecting the outermost layer may be integrally formed on the outer side of the outermost layer 1. The protective layer improves the durability of the plastic scintillation fiber. The material for the protective layer is not particularly limited, but from the viewpoint of productivity, it is preferable that the protective layer be a thermoplastic resin that can be molded integrally with the outermost layer 1.
[0042] <Modification of plastic scintillation fiber> FIG. 2 is a cross-sectional view of a plastic scintillation fiber according to a modified example of the first embodiment. As shown in FIG. 2, a reflective layer 5 may be provided on the surface of the outermost layer 1 or the protective layer. The scintillation light emitted by the outermost layer 1 and the light wavelength-converted by the core 2 are reflected by the reflective layer 5, making them less likely to leak out from the side of the fiber, resulting in high luminescence. Here, by making the reflective layer 5 a metal film, a high reflectance can be obtained with a thin thickness. On the other hand, since the metal film has a high probability of interacting with X-rays and gamma rays, by making the thickness thicker, the sensitivity to X-rays and gamma rays is improved, and the utilization efficiency of the light wavelength-converted by the core 2 and the scintillation light emitted by the outermost layer 1 is also increased, resulting in high luminescence.
[0043] 3 is a cross-sectional view of a plastic scintillation fiber according to another modification of the first embodiment. The plastic scintillation fiber according to the other modification has clad layer 3 as an inner clad layer and further has clad layer 4 as an outer clad layer. That is, the clad layer has a multi-clad structure including an inner clad layer (clad layer 3) and an outer clad layer (clad layer 4). Clad layer 4 covers the outer peripheral surface of clad layer 3 and is made of a transparent resin with a lower refractive index than clad layer 3.
[0044] Here, the re-emitted light that has been wavelength converted in core 2 is radiated isotropically in terms of solid angle within core 2. Therefore, only light within a total reflection angle based on the refractive index difference between core 2 and cladding layer 3 or cladding layer 4 can be transmitted in the fiber direction. The plastic scintillation fiber according to another modification includes cladding layer 4 with a low refractive index in addition to cladding layer 3, and therefore has a wider total reflection angle (larger numerical aperture NA) than the plastic scintillation fiber of Fig. 1, resulting in higher light emission.
[0045] <Material of outermost layer 1> The outermost layer 1, which is a scintillator layer, is made of a transparent resin having scintillation properties and containing a compound of a heavy metal element. The transparent resin having scintillation properties constituting the outermost layer 1 is preferably thermoplastic so that it can be drawn into a thin line by heating. As such a transparent resin, a homopolymer or copolymer made of aromatic monomers having a vinyl group, such as styrene, is preferable.
[0046] The outermost layer 1 may contain a transparent resin that does not have scintillation properties. Examples of such transparent resins include homopolymers or copolymers made of either a methacrylic acid ester monomer group represented by methyl methacrylate or an acrylic acid ester monomer group represented by methyl acrylate.
[0047] It is desirable for the heavy metal compound to be highly soluble in aromatic monomers with a vinyl group, such as styrene, which is stable and has scintillation properties. High solubility increases the transparency of the polymer obtained by dissolving the heavy metal compound in an aromatic monomer and polymerizing it. Poor solubility makes it difficult to disperse uniformly in the plastic scintillation material, resulting in problems such as variations in detection sensitivity to X-rays and gamma rays. Also, if dispersed as a powder, it becomes difficult to draw a line by heating. Alternatively, the compound of the heavy metal element may be a monomer that is copolymerizable with the monomer that is the raw material of the transparent resin.
[0048] Suitable lead compounds include lead(II) methacrylate, lead(IV) acetate, lead(II) citrate, lead naphthenate, lead(II) octoate, lead(II) stearate, lead(II) formate, lead(II) tartrate, lead(II) cyclohexanoate, lead(II) 2-ethylhexylate, and other carboxylates of lead, as well as lead(II) acetylacetonate, lead(II) hexafluoroacetylacetonate, bis(2,2,6,6-tetramethyl-3,5-heptanedionato)lead, tetraphenyllead, diphenyllead dichloride, tetraphenyl(phenylethynyl)lead(IV), lead(II) metavanadate, lead(II) titanate, lead(II) zirconate, lead(II) arsenate, and lead hexafluorosilicate.
[0049] Suitable examples of bismuth compounds include bismuth carboxylates such as bismuth subgallate (III), bismuth subsalicylate (III), bismuth methacrylate (III), bismuth acrylate (III), bismuth neodecanoate (III), bismuth oxyacetate (III), bismuth benzoate (III), bismuth citrate (III), and bismuth tris(2-ethylhexanoate) (III); bismuth compounds such as triphenylbismuthine, tri-para-tolylbismuthine, and tris(2-methoxyphenyl)bismuthine; bismuth alkoxide compounds such as tri-i-propoxybismuth, triethoxybismuth, and tri-t-amyloxybismuth; and bismuth chelate complexes such as tris(dipivaloylmethanato)bismuth. The carboxylic acid of the carboxylate and the alcohol of the alkoxide may each be a combination of two or more compounds rather than a single compound.
[0050] The wavelength conversion phosphor contained in the outermost layer 1 is preferably an organic phosphor having an aromatic ring and a resonant structure, and is monomolecularly dissolved in the core 2. Representative phosphors that absorb light at 250 to 350 nm include 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD), 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole (PBD), para-terphenyl (PTP), para-quaterphenyl (PQP), 2,5-diphenyloxazole (PPO), 1-phenyl-3-(2,4,6-trimethylphenyl)-2-pyrazoline (PMP), 3-hydroxyflavone (3HF), and the like.
[0051] Also preferred are 4,4'-bis-(2,5-dimethylstyryl)-diphenyl (BDB), 2,5-bis-(5-t-butyl-benzoxazoyl)thiophene (BBOT), 1,4-bis-(2-(5-phenyloxazolyl))benzene (POPOP), 1,4-bis-(4-methyl-5-phenyl-2-oxazolyl)benzene (DMPOPOP), 1,4-diphenyl-1,3-butadiene (DPB), 1,6-diphenyl-1,3,5-hexatriene (DPH), and the like, which absorb at 350 to 400 nm.
[0052] Examples of the outermost layer 1 include polystyrene copolymerized with lead methacrylate and a phosphor that converts the scintillation light of polystyrene to a longer wavelength. The inclusion of heavy metal elements lead and bismuth increases the probability of generating charged particles such as positrons and electrons due to the photoelectric effect, Compton effect, and electron pair creation when irradiated with X-rays or gamma rays. The charged particles generated here cause the outermost layer 1 to emit light due to the scintillation light emitted by the polystyrene contained in the outermost layer 1.
[0053] Another example of the outermost layer 1 is polystyrene containing triphenylbismuth and a phosphor that converts the scintillation light of the polystyrene to a longer wavelength. The inclusion of bismuth, a heavy metal element, increases the probability of generating charged particles such as positrons and electrons due to the photoelectric effect, Compton effect, electron pair creation, etc. when irradiated with X-rays or gamma rays. The charged particles generated here cause the outermost layer 1 to emit light due to the scintillation light emitted by the polystyrene contained in the outermost layer 1.
[0054] The types of the compound of the heavy metal element, the resin having scintillation properties, and the wavelength conversion phosphor are not limited to those described above. The compounding ratios and concentrations of the above materials are appropriately selected depending on the degree of difficulty of production, and are not limited to those described above.
[0055] <Core 2 Materials> There are no restrictions on the material used for the core 2 so long as it is a transparent resin. Among them, a homopolymer or copolymer made of any one of a methacrylic acid ester monomer group represented by methyl methacrylate, an acrylic acid ester monomer group represented by methyl acrylate, and an aromatic monomer group having a vinyl group represented by styrene is preferable.
[0056] Among them, a polymer made of an aromatic monomer having a vinyl group is preferable because it has a high refractive index. The refractive index difference between the core 2 and the cladding layer 3 becomes large, and the total reflection angle becomes wide. In other words, among the light wavelength-converted in the core 2, light with a wider angle can be transmitted, resulting in a scintillation fiber with higher luminescence.
[0057] The wavelength conversion phosphor contained in the core 2 is preferably an organic phosphor having an aromatic ring and a resonant structure, and is monomolecularly dissolved in the core 2. Representative phosphors that absorb light at 250 to 350 nm include 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD), 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole (PBD), para-terphenyl (PTP), para-quaterphenyl (PQP), 2,5-diphenyloxazole (PPO), 1-phenyl-3-(2,4,6-trimethylphenyl)-2-pyrazoline (PMP), and 3-hydroxyflavone (3HF).
[0058] Also preferred are 4,4'-bis-(2,5-dimethylstyryl)-diphenyl (BDB), 2,5-bis-(5-t-butyl-benzoxazoyl)thiophene (BBOT), 1,4-bis-(2-(5-phenyloxazolyl))benzene (POPOP), 1,4-bis-(4-methyl-5-phenyl-2-oxazolyl)benzene (DMPOPOP), 1,4-diphenyl-1,3-butadiene (DPB), 1,6-diphenyl-1,3,5-hexatriene (DPH), and the like, which absorb at 350 to 400 nm.
[0059] In order to obtain high light emission, it is preferable that the absorption spectrum of the wavelength conversion phosphor contained in the core 2 and the emission spectrum of the phosphor contained in the outermost layer 1 overlap widely. The above-mentioned wavelength conversion phosphors may be used alone, or multiple wavelength conversion phosphors may be used in combination. It is preferable that each wavelength conversion phosphor has a high quantum yield and little overlap between the absorption spectrum and the emission spectrum (a large Stokes shift). Since the longer the wavelength is, the smaller the transmission loss of visible light is, as a characteristic of plastic fibers, wavelength conversion phosphors that emit light at longer wavelengths are preferable, and two or more types may be used in combination as appropriate. It is preferable that the wavelength conversion phosphor is soluble in the transparent resin that constitutes the core 2.
[0060] The concentration of the wavelength conversion phosphor, whether it is a single one or a plurality of wavelength conversion phosphors, is preferably 50 to 10,000 ppm by mass concentration, more preferably 100 to 1,000 ppm. If the concentration is too low, the scintillation light from the outermost layer 1 cannot be efficiently absorbed in the core 2. On the other hand, if the concentration is too high, the effect of self-absorption of the phosphor itself becomes large, reducing the wavelength conversion efficiency or reducing the transmittance of the converted light, thereby worsening the attenuation length.
[0061] <Material of Clad Layer 3> There are no restrictions on the material used for the cladding layer 3, so long as it is a transparent resin having a lower refractive index than the core 2. Among them, homopolymers or copolymers made from any of the following raw materials are preferable: methacrylic acid ester monomers represented by methyl methacrylate, fluorinated monomers such as perfluoroalkyl methacrylate, and acrylic acid ester monomers represented by methyl acrylate, and fluorinated monomers such as perfluoroalkyl acrylate.
[0062] <Material of Clad Layer 4> The material used for the cladding layer 4 may be any transparent resin having a refractive index lower than that of the cladding layer 3. It may be selected from the monomer group of the cladding layer 3. In particular, it is preferable to select from a fluorine-containing monomer group having a low refractive index.
[0063] These monomers can be easily polymerized or copolymerized by heat or light irradiation, and have the advantage that the refractive index can be easily adjusted by the composition and that they are easy to handle. An organic peroxide or an azo compound may be added as a polymerization initiator during polymerization. Representative organic peroxides include 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, n-butyl-4,4-bis(t-butylperoxy)valerate, and 1,1-bis(t-butylperoxy)cyclohexane, but there are no particular limitations as long as they generate radicals by heat or light irradiation.
[0064] Mercaptan may be added as a chain transfer agent to adjust the molecular weight. A typical example of mercaptan is octyl mercaptan, but there is no particular restriction as long as it has the R-SH (where R represents an organic group) structure.
[0065] <Reflective layer material> There are no restrictions on the material constituting the reflective layer 5 as long as it is a material that can reflect light emitted from the side surface of the fiber with high reflectance. Among them, a metal film is preferable because it can obtain high reflectance with a thinner thickness and further improves sensitivity to X-rays and gamma rays compared to, for example, white reflective paint.
[0066] The metal film is not particularly limited as long as it has a high reflectance in the required wavelength range, such as aluminum, gold, silver, nickel, etc. Aluminum and silver are preferable because of their high reflectance in the visible light range. Furthermore, aluminum is preferable from the viewpoint of cost.
[0067] The thickness of the metal film is not particularly limited, but it is preferable to obtain a high reflectance in the visible light region with a thickness as thin as possible. For example, for aluminum, the thickness is preferably 10 to 100 nm, more preferably 20 to 70 nm. For silver, the thickness is preferably 35 to 150 nm, more preferably 50 to 100 nm. On the other hand, if there is no limit to the diameter of the fiber, the metal film may be thickened as much as possible. By making the metal film thicker, the sensitivity to X-rays and gamma rays is further improved. The film formation method is not particularly limited and may be a deposition method, a sputtering method, or the like.
[0068] <Manufacturing method of plastic scintillation fiber> 4 is a perspective view showing a manufacturing method of a plastic scintillation fiber according to the embodiment 1. FIG 4 shows a base material (preform) for manufacturing the plastic scintillation fiber shown in FIG.
[0069] The first cylinder 11 is a cylinder made of a thermoplastic resin having scintillation properties, which contains a compound of a heavy metal element. The thermoplastic resin contains a phosphor that converts the scintillation light it emits into a light having a long wavelength. The first cylinder 11 constitutes the outermost layer 1 after drawing.
[0070] The rod 12 is a cylindrical body made of a transparent thermoplastic resin in which at least one type of phosphor that absorbs scintillation light and converts it to a longer wavelength is dissolved. The rod 12 constitutes the core 2 after being drawn. The second cylinder 13 is a cylinder made of a transparent thermoplastic resin and has a lower refractive index than the rod 12. The second cylinder 13 constitutes the cladding layer 3 after the drawing process.
[0071] As shown in Fig. 4, a preform is produced by inserting a second cylinder 13 into a first cylinder 11 and inserting a rod 12 into the second cylinder 13. Fig. 4 shows a state in the middle of inserting the rod 12 into the second cylinder 13. The tip of the produced preform is heated and drawn to an outer diameter of, for example, 1 mm, to obtain the plastic scintillation fiber according to the first embodiment.
[0072] As shown in FIG. 4, gaps are formed between the first cylinder 11, the second cylinder 13, and the rod 12. However, since the wire drawing process is performed under reduced pressure, the core 2, the cladding layer 3, and the outermost layer 1 are tightly adhered and integrally formed. The plastic scintillation fiber according to the modified example shown in FIG. 3 can be manufactured by the same manufacturing method.
[0073] In the manufacturing method of the plastic scintillation fiber according to the first embodiment, a scintillator layer (outermost layer 1) containing a compound of a heavy metal element is integrally formed on the outer peripheral surface of the wavelength conversion fiber (core 2 and cladding layer 3). Therefore, the plastic scintillation fiber is capable of detecting X-rays and gamma rays and transmitting light. In other words, the plastic scintillation fiber is a scintillator-integrated plastic wavelength conversion fiber that has the functions of both a conventional scintillator and a wavelength conversion fiber by itself.
[0074] Therefore, the post-processing required for combining the scintillator and wavelength conversion fiber, which was previously required, is no longer necessary, and productivity is improved and costs are reduced compared to the past. In particular, when detecting images, there is no need to separate and combine each scintillator for each wavelength conversion fiber, and it is sufficient to simply line up the plastic scintillation fibers. Therefore, productivity is dramatically improved and costs are reduced compared to the past.
[0075] After the wavelength conversion fiber (core 2 and cladding layer 3) is manufactured, a scintillator layer (outermost layer 1) may be integrally formed on the surface of the wavelength conversion fiber by coating (including painting).
[0076] <Applications of plastic scintillation fibers> Next, an application example of the plastic scintillation fiber according to the first embodiment will be described with reference to Fig. 5. Fig. 5 is a perspective view showing an application example of the plastic scintillation fiber according to the first embodiment. In this application example, the plastic scintillation fibers PSF according to the first embodiment are arranged in an array on a substrate. Naturally, the right-handed xyz Cartesian coordinate system shown in Fig. 5 is a convenient way to explain the positional relationship of the components. Usually, the positive direction of the z axis is vertically upward, and the xy plane is a horizontal plane.
[0077] A photoelectric detector such as a photomultiplier tube (not shown) is connected to each plastic scintillation fiber (PSF) to detect the transmitted light. This configuration enables one-dimensional image detection (position detection) with a resolution of, for example, 1 mm, where the resolution is equal to the diameter of the plastic scintillation fiber PSF. Furthermore, if two such arrays of plastic scintillation fibers (PSF) are provided and arranged perpendicular to each other and stacked one on top of the other, two-dimensional image detection can also be achieved.
[0078] In this way, image detection of X-rays or gamma rays with high spatial resolution can be realized easily and at low cost by using the plastic scintillation fiber according to this embodiment. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0080] <Example 1> 20% by mass of lead methacrylate and 1% by mass of the phosphor 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD) were added to styrene monomer and copolymerized to form a cylinder for the outermost layer (first cylinder 11 in Figure 4) with an outer diameter of 95 mm and an inner diameter of 71 mm.
[0081] A core rod (rod 12 in FIG. 4) made of polystyrene (refractive index 1.59) with a diameter of 65 mm and a cladding layer cylinder (second cylinder 13 in FIG. 4) made of polymethyl methacrylate (refractive index 1.49) with an outer diameter of 70 mm and an inner diameter of 66 mm were prepared. 2,5-bis-(5-t-butyl-benzoxazoyl)thiophene (BBOT) was dissolved in the core rod as a wavelength conversion phosphor at a concentration of 200 ppm by mass.
[0082] As shown in Fig. 4, a cylinder for cladding layer was inserted into a cylinder for the outermost layer, and a core rod was inserted into the cylinder for cladding layer to prepare a preform. While heating the tip of this preform, it was integrally drawn under reduced pressure to an outer diameter of 1 mm, to obtain a plastic scintillation fiber according to Example 1. This plastic scintillation fiber has the cross-sectional configuration shown in Fig. 1. The outer diameter was 1 mm, the diameter of the cladding layer 3 was 0.72 mm, the diameter of the core 2 was 0.68 mm, the thickness of the outermost layer 1 was 0.14 mm, and the thickness of the cladding layer 3 was 0.02 mm.
[0083] 6 is a graph showing the emission spectrum of the phosphor 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD) and the absorption and emission spectra of the wavelength conversion phosphor BBOT added to the outermost layer 1. As shown in FIG. 6, there is a large overlap between the emission spectrum of the outermost layer 1 and the absorption spectrum of the wavelength conversion phosphor.
[0084] The plastic scintillation fiber of Example 1 contains lead element in the outermost layer 1, which has a higher probability of interaction with X-rays and gamma rays than light elements such as carbon, hydrogen, and oxygen, and therefore has improved detection sensitivity for X-rays and gamma rays compared to conventional plastic scintillation fibers.
[0085] <Example 2> As in Example 1, a cylinder for the outermost layer (first cylinder 11 in FIG. 4) having an outer diameter of 95 mm and an inner diameter of 76 mm was molded. Also, as in Example 1, a core rod (rod 12 in FIG. 4) made of polystyrene (refractive index 1.59) having a diameter of 65 mm and a cylinder for the inner clad layer (second cylinder 13 in FIG. 4) made of polymethyl methacrylate (refractive index 1.49) having an outer diameter of 70 mm and an inner diameter of 66 mm were prepared. In the core rod, BBOT was dissolved as a wavelength conversion phosphor at a concentration of 300 ppm by mass.
[0086] Furthermore, in Example 2, a cylinder for an outer clad layer (not shown) was prepared, which was made of a copolymer (refractive index 1.42) of a fluorinated monomer such as perfluoroalkyl acrylate and had an outer diameter of 75 mm and an inner diameter of 71 mm. The cylinder for the outer clad layer constitutes the clad layer 4 shown in FIG. 3 after drawing. Then, a cylinder for an outer clad layer was inserted inside the cylinder for the outermost peripheral layer, a cylinder for an inner clad layer was inserted inside that, and a core rod was inserted inside that, to prepare a preform.
[0087] While heating the tip of this preform, it was integrally drawn under reduced pressure so that the outer diameter became 1 mm, thereby obtaining a plastic scintillation fiber according to Example 2. This plastic scintillation fiber has the cross-sectional configuration shown in Fig. 3. The outer diameter was 1 mm, the outer diameter of cladding layer 4 was 0.76 mm, the outer diameter of cladding layer 3 was 0.72 mm, the diameter of core 2 was 0.68 mm, the thickness of outermost layer 1 was 0.12 mm, the thickness of cladding layer 4 was 0.02 mm, and the thickness of cladding layer 3 was 0.02 mm.
[0088] When X-rays were incident on the plastic scintillation fiber of Example 2, a light quantity about 30% higher than that of Example 1 was observed at the tip 10 m away. Although the diameter of the core 2 was smaller than that of Example 1, it is believed that the provision of the cladding layer 4 with a lower refractive index widened the total reflection angle, resulting in higher light emission.
[0089] <Example 3> 10% by mass of triphenylbismuth and 1% by mass of the phosphor 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD) were added to styrene monomer and polymerized, and then a cylinder for the outermost layer (first cylinder 11 in Figure 4) with an outer diameter of 95 mm and an inner diameter of 71 mm was molded from the monomer.
[0090] A core rod (rod 12 in FIG. 4) made of polystyrene (refractive index 1.59) with a diameter of 65 mm and a cladding layer cylinder (second cylinder 13 in FIG. 4) made of polymethyl methacrylate (refractive index 1.49) with an outer diameter of 70 mm and an inner diameter of 66 mm were prepared. 2,5-bis-(5-t-butyl-benzoxazoyl)thiophene (BBOT) was dissolved in the core rod as a wavelength conversion phosphor at a concentration of 200 ppm by mass.
[0091] As shown in Fig. 4, a cylinder for cladding layer was inserted into a cylinder for the outermost layer, and a core rod was inserted into the cylinder for the cladding layer to prepare a preform. While heating the tip of this preform, it was integrally drawn under reduced pressure to an outer diameter of 1 mm, to obtain a plastic scintillation fiber according to Example 3. This plastic scintillation fiber has the cross-sectional configuration shown in Fig. 1. The outer diameter was 1 mm, the diameter of the cladding layer 3 was 0.72 mm, the diameter of the core 2 was 0.68 mm, the thickness of the outermost layer 1 was 0.14 mm, and the thickness of the cladding layer 3 was 0.02 mm.
[0092] The plastic scintillation fiber of Example 3 contains bismuth element in the outermost layer 1, which has a higher probability of interaction with X-rays and gamma rays than light elements such as carbon, hydrogen, and oxygen, and therefore has improved detection sensitivity for X-rays and gamma rays compared to conventional plastic scintillation fibers.
[0093] <Example 4> An aluminum film was formed on the surface of the plastic scintillation fiber of Example 1 by vapor deposition to a thickness of about 50 nm. The scintillation light emitted in the outermost layer 1 and the light whose wavelength has been converted in the core 2 are reflected by the reflective layer 5, making them less likely to leak out from the side surface of the fiber, resulting in high luminescence.
[0094] The present invention is not limited to the above-described embodiment, and can be modified as appropriate without departing from the spirit and scope of the present invention.
[0095] This application claims priority based on Japanese Patent Application No. 2020-173826, filed on October 15, 2020, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]
[0096] 1 Outermost layer 2 cores 3. Clad layer (inner clad layer) 4 Clad layer (outer clad layer) 5 Reflective layer 11 First Cylinder 12 Rod 13 Second Cylinder PSF Plastic Scintillation Fiber
Claims
1. an outermost layer including a resin containing a compound of a heavy metal element and having scintillation properties, and at least one type of first phosphor that absorbs scintillation light emitted by the resin and converts the wavelength of the light to a longer wavelength; a core provided inside the outermost layer and including at least one type of second phosphor that absorbs light emitted by the first phosphor in the outermost layer and converts the light to a longer wavelength; a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core; a wavelength conversion fiber including the core and the cladding layer and the outermost layer covering an outer peripheral surface of the wavelength conversion fiber are integrally formed, The scintillation light absorbed by the first phosphor is ultraviolet light having a wavelength of 250 to 350 nm, The second phosphor absorbs light having a wavelength of 350 to 400 nm emitted by the first phosphor and converts it into light having a longer wavelength. Plastic scintillating fiber.
2. The heavy metal element is lead.
2. The plastic scintillation fiber according to claim 1.
3. The heavy metal element is bismuth.
2. The plastic scintillation fiber according to claim 1.
4. In the outermost layer, the compound of the heavy metal element is copolymerized with the resin having scintillation properties. The plastic scintillation fiber according to any one of claims 1 to 3.
5. the wavelength conversion fiber and the outermost layer are integrally formed by a drawing process; The plastic scintillation fiber according to any one of claims 1 to 4.
6. A protective layer for protecting the outermost layer is integrally formed on the outer side of the outermost layer. The plastic scintillation fiber according to any one of claims 1 to 5.
7. The cladding layer is An inner clad layer; and an outer clad layer covering the outer peripheral surface of the inner clad layer and having a refractive index lower than that of the inner clad layer. The plastic scintillation fiber according to any one of claims 1 to 6.
8. A reflective layer is provided on the outer side of the outermost layer. The plastic scintillation fiber according to any one of claims 1 to 5.
9. A reflective layer is provided on the outer side of the protective layer.
7. The plastic scintillation fiber according to claim 6.
10. The reflective layer is a metal film.
10. The plastic scintillation fiber according to claim 8 or 9.
11. an outermost layer including a resin containing a compound of a heavy metal element and having scintillation properties, and at least one type of first phosphor that absorbs scintillation light emitted by the resin and converts the wavelength of the light to a longer wavelength; a core provided inside the outermost layer and including at least one type of second phosphor that absorbs light emitted by the first phosphor in the outermost layer and converts the light to a longer wavelength; A method for manufacturing a plastic scintillation fiber comprising: a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core, a step of inserting a second cylinder for the cladding layer into a first cylinder for the outermost layer, and inserting the core rod into the second cylinder to prepare a preform; and a step of drawing the preform while heating it. The scintillation light absorbed by the first phosphor is ultraviolet light having a wavelength of 250 to 350 nm, The second phosphor absorbs light having a wavelength of 350 to 400 nm emitted by the first phosphor and converts it into light having a longer wavelength. A method for manufacturing plastic scintillation fibers.
12. an outermost layer including a resin containing a compound of a heavy metal element and having scintillation properties, and at least one type of first phosphor that absorbs scintillation light emitted by the resin and converts the wavelength of the light to a longer wavelength; a core provided inside the outermost layer and including at least one type of second phosphor that absorbs light emitted by the first phosphor in the outermost layer and converts the light to a longer wavelength; A method for manufacturing a plastic scintillation fiber comprising: a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core, coating the outermost layer on a surface of the wavelength conversion fiber including the core and the cladding layer; The scintillation light absorbed by the first phosphor is ultraviolet light having a wavelength of 250 to 350 nm, The second phosphor absorbs light having a wavelength of 350 to 400 nm emitted by the first phosphor and converts it into light having a longer wavelength. A method for manufacturing plastic scintillation fibers.
Citation Information
Patent Citations
Transmission device for radiation ray detection light
JP1994201835A
High-efficiency, high-resolution and real-time radiographic imaging system
JP1994317713A
Fiber type radiation detector
JP1997236669A
Optical fiber and optical fiber cable
JP2000065939A
Pixel type two-dimensional image detector
JP2011141239A